The Development of Animated Powtoon Media in Teaching Personal and Official Letters for Grade 7 at SMPN 1 Sitiung - Amar Salahuddin; Aprimadedi Aprimadedi; Deviana Putri (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to develop Powtoon-based learning media on material to recognize personal letters and official letters for class VII students in Sitiung 1 Public Middle School. This study uses the Research and Development (R & D) method with a 4D development model, which includes the define stage, design, develop, and disseminate. This research was conducted at the Sitiung 1 Public Middle School in the 2024/2025 school year with the research subjects was a class VII student amounting to 31 people. Data collection techniques are carried out through questionnaire response students and teachers, as well as validation sheets involving media experts, material experts, and luition experts. The results of this study showed researchers to produce Powtoon-based learning media as material learning media comparing personal letters and official letters, the media said valid, seen from the validation of media experts obtained a score of 81.25% and included the